Muhammad Iqbal as a Cosmopolitan Philosopher - Saad Malook (بازیافت)
This article makes an exposition of the substantial cosmopolitan strands in Muhammad Iqbal’s writings. Cosmopolitanism is a philosophical approach that recognises human beings across nations to be members of a global tribe. This approach supports the idea of world citizenship, global state or global institutions. Individualism, egalitarianism and universalism are the key principles of cosmopolitanism. I argue that Iqbal is a cosmopolitan philosopher because his philosophical thinking is not only consistent with the core principles of cosmopolitanism but also contains essential cosmopolitan aspects, including intellectual, moral, and political. Iqbal postulates the idea of the human self that acquires the idea of a unique individuality which is compatible with egalitarianism and universalism in certain ways. Iqbal’s intellectual cosmopolitanism fosters the cognitive development of people for enhancing their creativity, which is based not only on the oriental and the occidental traditions but also on the intertemporal epochs with an interdisciplinary approach ranging primarily from philosophy, religion and literature to science. Intellectual cosmopolitanism produces creative human agency. Iqbal’s moral cosmopolitanism develops certain moral values to make human perfection and human fraternity. Iqbal’s political cosmopolitanism envisions a federation of states in which people practising spiritual democracy in the kingdom of ends on earth create and sustains global peace. These strands in Iqbal’s philosophical ideas create a creative human agency, human fraternity, reverence for humanity, and global peace, respectively. Thus, I argue that Iqbal meets all the conditions squarely to be a cosmopolitan philosopher.    Keywords: Cosmopolitanism, Nationalism, Ethics, Politics, Muslim Philosophy.